2005
DOI: 10.1152/ajpcell.00039.2005
|View full text |Cite
|
Sign up to set email alerts
|

Proton-sensing G protein-coupled receptor mobilizes calcium in human synovial cells

Abstract: -Lowered extracellular pH in a variety of tissues is associated with increased tissue destruction and initiation of inflammatory processes. Although the acid-sensing receptors described previously are ion channels, we describe a G protein-coupled proton-sensitive receptor that stimulates Ca 2ϩ release from intracellular stores in a tumor-derived synoviocyte cell line (SW982) and in primary cultures of human synovial cells from patients with inflammatory arthropathies. We established a link between proton-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…The TRP channel-mediated calcium response is independent of intracellular stores or concurrent activation of voltage-dependent calcium channels. In a previous study we demonstrated (6) that SW982 synoviocytes do not have ryanodine-sensitive calcium stores. Therefore, calcium-induced calcium release also does not contribute to calcium signaling in synovial cells.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The TRP channel-mediated calcium response is independent of intracellular stores or concurrent activation of voltage-dependent calcium channels. In a previous study we demonstrated (6) that SW982 synoviocytes do not have ryanodine-sensitive calcium stores. Therefore, calcium-induced calcium release also does not contribute to calcium signaling in synovial cells.…”
Section: Discussionmentioning
confidence: 87%
“…An acidsensing G protein-coupled receptor has been identified on synovial cells that are responsive to low pH (pH 5.5-7.0) in calcium-free media except in the presence of Cu 2ϩ (6). A response profile in low pH (pH 7.0 -7.2) in the presence of Cu 2ϩ was also noted, consistent with transient receptor potential (TRP)V1 activation.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Measurement of intracellular Ca 2+ levels helps to elucidate functional changes of Ca 2+ -permeable channels in the plasma membrane or intracellular organelles and the contribution of Ca 2+ to the above processes (9-13). The assay can also be used to investigate the function of G-protein coupled receptors, many of which, upon activation, lead to increased intracellular free Ca 2+ concentrations by releasing Ca 2+ from intracellular Ca 2+ stores or activating other Ca 2+ permeable ion channels (14)(15)(16). FlexStation 3 makes use of Ca 2+ sensitive dyes, which give rise to increased fluorescence intensity, or ratiometric changes, with the increase of intracellular Ca 2+ concentration.…”
Section: Data Analysis 7 Representative Resultsmentioning
confidence: 99%
“…These synoviocytes express many biological sensors including receptors and ion channels (1,2,9,10). In the chronic inflammation and pain associated with rheumatoid arthritis and injury, some of these sensors are active, implying that they are potential targets for treatment.…”
mentioning
confidence: 99%